The MOSDEF survey: differences in SFR and metallicity for morphologically selected mergers at z ∼ 2. Issue 1 (18th November 2020) - Horstman, Katelyn; Shapley, Alice E; Sanders, Ryan L; Mobasher, Bahram; Reddy, Naveen A; Kriek, Mariska; Coil, Alison L; Siana, Brian; Shivaei, Irene; Freeman, William R; Azadi, Mojegan; Price, Sedona H; et al.
ABSTRACT: We study the properties of 55 morphologically-identified merging galaxy systems at z ∼ 2. These systems are flagged as mergers based on features such as tidal tails, double nuclei, and asymmetry. Our sample is drawn from the MOSFIRE Deep Evolution Field (MOSDEF) survey, along with a control sample of isolated galaxies at the same redshift. We consider the relationships between stellar mass, star formation rate (SFR), and gas-phase metallicity for both merging and non-merging systems. In the local universe, merging systems are characterized by an elevated SFR and depressed metallicity compared to isolated systems at a given mass. Our results indicate SFR enhancement and metallicity deficit for merging systems relative to non-merging systems for a fixed stellar mass at z ∼ 2, though larger samples are required to establish these preliminary results with higher statistical significance. In future work, it will be important to establish if the enhanced SFR and depressed metallicity in high-redshift mergers deviate from the 'fundamental metallicity relation, ' as is observed in mergers in the local universe, and therefore shed light on gas flows during galaxy interactions.